Young adult carers' identification, characteristics, and support: A systematic review - Chevrier, Basilie; Lamore, Kristopher; Untas, Aurélie; Dorard, Géraldine (Frontiers in Psychology, 2022)
Young Adult Carers (YAC) are informal carers aged 18–25 years. This is an unrecognized population. The present systematic review aims to respond to: (1) how YAC are identified in research; (2) the prevalence of YAC; (3) the characteristics of YAC; and (4) how to support YAC. Five electronic databases (Google Scholar, PsycArticle, PsycInfo, Psychology and Behavioral Sciences Collection, and PubMed) were searched for studies, scientific articles, and grey literature on YAC published prior to January 18, 2021. The quality of included studies was assessed using the Crow Critical Appraisal Tool, and a narrative method was used to underline major findings. Twenty-three studies were included and revealed that there were several ways to identify YAC, resulting in heterogeneous prevalence. Nine themes were highlighted for YAC characteristics (way into caring; care receiver; caring responsibilities; amount of caring; self-identification as a carer; living arrangement; physical, psychological, and adaptative outcomes; interpersonal relationships; education and employment); and three for YAC support (needs, available support services, recommendations). The findings showed the diversity of YAC experiences. Although YAC expressed several needs, there are few or no support services devoted to them. More research is needed to improve political awareness.